Multidimensional targeting : identifying beneficiaries of conditional cash transfer programs - Azevedo, V; Robles, M (Oxford Poverty & Human Development Initiative (OPHI), 2010)
Conditional cash transfer programs (CCTs) have two main objectives: reduce poverty and increase the human capital of children. To reach these objectives, transfers are given to poor households conditioned on investments in their children’s education, health, and nutrition. Targeting mechanisms used by CCTs have been generally successful in identifying the income poor, but have not fared as well in identifying households that under-invest in human capital. These mechanisms do not consider the multidimensional aspect of poverty, even when composite measures are used, as it does not capture each dimension-specific deprivation. This paper proposes a multidimensional targeting approach to identifying beneficiaries that explicitly take in consideration the multiple objectives of the CCTs and the multiple deprivations of the poor household. Results indicate that the proposed multidimensional targeting methodology significantly improves the selection of households with children who are most deprived in the dimensions often relevant to CCTs. In the case of Mexico’s Oportunidades, ex-ante evaluation results indicate that the multidimensional identification of beneficiaries increases the welfare impact of transfers compared to alternative targeting models.